help me answer this question please. :) a picture is attached below.
![help me answer this question please a picture is attached below class=](https://us-static.z-dn.net/files/d42/4d14970792987234250dcf980c4b0f09.png)
Answer:
- 7[tex]x^{6}[/tex][tex]y^{9}[/tex]
Step-by-step explanation:
using the rule of exponents
[tex]a^{m}[/tex] × [tex]a^{n}[/tex] = [tex]a^{(m+n)}[/tex]
given
- 7x³[tex]y^{5}[/tex] (x³[tex]y^{4}[/tex])
= - 7 × x³ ×x³ ×[tex]y^{5}[/tex] × [tex]y^{4}[/tex]
= - 7 × [tex]x^{(3+3)}[/tex] × [tex]y^{(5+4)}[/tex]
= - 7[tex]x^{6}[/tex][tex]y^{9}[/tex]